KARAKTERISTIK PELAJAR PENYALAHGUNA NAPZA DAN JENIS NAPZA YANG DIGUNAKAN DI KOTA SURABAYA - Maydiya Restacendi Nur’artavia (The Indonesian Journal of Public Health, 2017)
Drug abusers increases every years, and the student is one of vulnarable group. The students are adolescence group who have emotional instability, and high couriousity about something new because they thinks they already adult. The purpose of this study was to describe drug abuse, and drug type of thestudent in Surabaya. The research was descriptive which analyzed secondary data in rehabilititation’s division BNN Kota Surabaya. The population of this study were the students in Surabaya during 2015. The purposive sampling was used to take sample in this study which consisted of 189 students whorecorded by BNN Kota Surabaya. The research was done at Agustus-September 2016 in BNN Kota Surabaya. The results showed that 80.95% the students were male, in the early teens (54.5%). Drug of Choice and drug most often used was double L with the amount of each 97.35%, and 88.89%, and most of the drug being abused was only one type (91.53%). Most of the students abused drug found in Sawahan and Tegalsari districts. It was concluded that most of the students who use drug were male, in early teen, using double L/Trihexyphenidyl, and coming from Sawahan and Tegalsari. Routine screening on students, and spot inspections need to be done.Keywords: drug abuser, drug type, the student